2022
DOI: 10.1172/jci150535
|View full text |Cite
|
Sign up to set email alerts
|

Neoantigen-reactive CD8+ T cells affect clinical outcome of adoptive cell therapy with tumor-infiltrating lymphocytes in melanoma

Abstract: BACKGROUND Neoantigen-driven recognition and T cell–mediated killing contribute to tumor clearance following adoptive cell therapy (ACT) with tumor-infiltrating lymphocytes (TILs). Yet how diversity, frequency, and persistence of expanded neoepitope-specific CD8 + T cells derived from TIL infusion products affect patient outcome is not fully determined. METHODS Using barcoded pMHC multimers, we provide a comprehensive mapping of CD8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 66 publications
2
60
0
Order By: Relevance
“…More recently, TILs have found their place in cancer treatment. Emerging data showed that adoptive cell therapy with TILs can be an effective treatment for metastatic melanoma [ 20 ]. Similarly, a recently published study demonstrated that cell therapy with autologous TILs may constitute a new treatment strategy in metastatic lung cancer [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, TILs have found their place in cancer treatment. Emerging data showed that adoptive cell therapy with TILs can be an effective treatment for metastatic melanoma [ 20 ]. Similarly, a recently published study demonstrated that cell therapy with autologous TILs may constitute a new treatment strategy in metastatic lung cancer [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…No dose-limited toxicity or cytokine release syndrome was observed, and no apparent autoimmune response occurred. Kristensen et al 151 performed ACT in patients with melanoma, finding that the number and frequency of new epitope-specific T cells in TILs infusion products were associated with improved clinical outcomes.…”
Section: Neoantigen Vaccine and Clinical Applicationmentioning
confidence: 99%
“…A phase II trial showed that 40 days after infusion of ex vivo amplified TILs that contained specific CD8+ T cells targeting neoepitope derived from the KRAS mutation G12D, a patient with metastatic colorectal cancer encountered regression of all the metastatic lung lesions, suggesting an important role of neoepitope-reactive CD8+ T cells in cancer therapy ( 51 ). Further research shows that TIL adoptive treatment is linked to an increase in neoepitope-specific CD8+ T cells ( 55 ). On the other hand, TIL-based ACT responders retained a subset of stem-like neoantigen-specific CD8+ T cells that show self-renewal and superior growth capacity in vitro and in vivo , highlighting the relevance of T-cell phenotypes in ACT response ( 56 ).…”
Section: Identification Of Immunogenic Neoantigensmentioning
confidence: 99%